INFLUENCE OF NONLINEARITY ON AVIATION SATELLITE COMMUNICATION CHANNEL PARAMETERS - Kharchenko, Volodymyr; Grekhov, Andrii; Ali, Ismail (Proceedings of National Aviation University (archive), 2016)
For an investigation of satellite amplifier nonlinearity impact on aviation OFDM communication channel parameters the original model of a link "Aircraft-Satellite-Ground Station" was built using MATLAB Sіmulіnk software. The model with adaptive modulation consists of a source of information, aircraft transmitter, uplink/downlink path, satellite transponder, and ground station receiver. The dependencies of a signal to noise ratio on free space path loss for different types of amplifier nonlinearity, signals modulation (BPSK, QPSK, 16QAM, 64QAM), noise temperatures were received. The spectrums and signals constellations of received signals were compared for different types of amplifier nonlinearity. Developed model allows predicting spectral regrowth of digitally modulated OFDM signals due to amplifier nonlinearity.